2016
DOI: 10.1111/jog.13210
|View full text |Cite
|
Sign up to set email alerts
|

Liver dysfunction in women with pregnancy‐induced antithrombin deficiency

Abstract: PIATD can occur in the absence of thrombocytopenia and PIATD women had higher risk of liver dysfunction even in the absence of thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…The risk of liver dysfunction increased with decreasing AT activity (Fig. ), confirming the results of retrospective studies . This suggested that use of AT activity was helpful for identifying women at risk of liver dysfunction.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The risk of liver dysfunction increased with decreasing AT activity (Fig. ), confirming the results of retrospective studies . This suggested that use of AT activity was helpful for identifying women at risk of liver dysfunction.…”
Section: Discussionsupporting
confidence: 79%
“…First, not all of the women underwent postnatal laboratory tests. We assumed that these women with unavailable postnatal data on AST and LDH did not have liver dysfunction based on our previous findings that none developed perinatal liver dysfunction in consecutive 127 women with perinatal AT activity > 65% . Second, the present cohort included larger numbers of women with HDP and twin pregnancies than the general population and therefore did not represent the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Women with PIATD are affected by decreased plasma volume and are more likely to develop liver dysfunction . Thus, low antithrombin activity is a risk for HELLP syndrome or acute fatty liver in pregnancy . Furthermore, low antithrombin activity is a risk factor for eclampsia .…”
Section: Discussionmentioning
confidence: 99%
“…As compared with women without HDP in peripartum-1 (233/257, 90.7%), those with HDP (24/257, 9.3%) were significantly older in both the first (35 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] In contrast, there were no significant differences in pre-pregnancy BMI for either the first or second pregnancy, or in the time between the first delivery and second pregnancy (22.2 [2.8-41.9] months vs 21.7 [2.1-85.7] months, P=0.483) between women with and those without HDP in peripartum-1 (Table 1). Birthweight was lower for women with HDP in peripartum-1 than for women without HDP in day −1/0 before the first delivery ( Fig.…”
Section: Characteristics Of Women With and Without Hdp In The Firstmentioning
confidence: 95%
See 1 more Smart Citation